The Influence Of Marketing Mix Strategy On Sales Increase With Purchasing Decisions As A Mediating Variable At The Keris Center, Aeng Tong-Tong Village, Sumenep - Nur Qoudri Wijaya; Moh. Baqir Ainun (UNIVED Press, 2025)
This study aims to analyze the effect of marketing mix strategies (product, price, place, and promotion) on increasing sales, with purchasing decisions as a mediating variable at the Keris Center of Aeng Tong-Tong Village, Sumenep. The research method used is a quantitative approach. Data were collected through a survey using a questionnaire distributed to 60 respondents. Data analysis techniques were carried out using multiple regression models and path analysis to test the direct and indirect effects between research variables. The results showed that only the price element in the marketing mix had a significant effect on purchasing decisions, while product, place, and promotion did not show a significant effect. In addition, purchasing decisions had a significant effect on increasing sales, indicating its role as a mediating variable. The indirect relationship shows that price affects sales increases through purchasing decisions, while other marketing mix elements are not significant. These findings emphasize the importance of determining the right pricing strategy to increase purchasing and sales decisions, while other elements in the marketing mix need to be optimized to be more effective in supporting the development of the Keris Center of Aeng Tong-Tong Village.